Peran Karel Frederick Holle dalam Perkembangan Pertanian dan Pendidikan di Garut - Diky Muhammad Marzuki (UIN Sunan Gunung Djati Bandung, 2019)
This paper discusses a very important figure in the development of language and literature in the city of Garut. Karel Frederick Holle was a Dutchman who came to the Indies at the age of 14 years. He began life in the Dutch East Indies as a housing administration employee in Cianjur. Followed by becoming a Dutch government employee in Batavia and ended up being an honorary advisor for land affairs in the administration department as well as a tea and coffee plantation owner in Cikajang Garut. This paper discusses K. F. Holle in outline. The author is aware of the lack of sources used due to the rare sources about K. F. Holle, therefore it needs further research in order to discuss all aspects in depth. Kata Kunci: Dutch Policy, Indonesian farming, K. F. Holle